2021
DOI: 10.1186/s41155-021-00185-w
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a training program for social skills in reducing addictive Internet behaviors among Palestinian university students

Abstract: Background For youth in geopolitically at-risk environments, such as Palestine, the issues related to Internet overuse and addictions are complex. Youth residing in the occupied territories of Palestine as in other highly militarized zones have high levels of environmental stressors (e.g., militarization, poverty, lack of employment opportunities, cultural pressures, etc.) and few chemical or social outlets such as alcohol, intoxicants, and leisure activities. As such, the easily accessible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
9
0
3
Order By: Relevance
“…Moreover, Internet addiction is proven to be closely related to attention deficit disorders, further causing social phobia [ 84 ]. Another study has identified that inadequate social skills and social fears decrease interpersonal communication [ 85 ]. Consequently, Internet use may hinder interpersonal interactions by reducing people’s social skills.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Internet addiction is proven to be closely related to attention deficit disorders, further causing social phobia [ 84 ]. Another study has identified that inadequate social skills and social fears decrease interpersonal communication [ 85 ]. Consequently, Internet use may hinder interpersonal interactions by reducing people’s social skills.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, compared with traditional communication methods, such as phone calls and text messages, the Internet helps people to establish a much wider social network and achieve effective remote communication at a lower cost, as well as with greater efficiency [ 69 , 70 , 90 , 101 ]. Nevertheless, other studies reveal that Internet usage may distract people’s attention [ 10 , 11 , 65 , 66 , 83 ], reduce their social skills [ 47 , 67 , 68 , 84 , 85 ], and may even increase negative emotions [ 10 , 11 , 53 , 73 , 86 ]. The impact of Internet usage in this aspect would hinder interpersonal communications.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…İspanya'da 12-16 yaş arası ergenlerle yapılan bir çalışmada problemli internet kullanımı olan ergenlerin sosyal kaygı ve sosyal beceri güçlüklerinde daha yüksek puanlar sergiledikleri bulunmuştur (44). Yapılan çalışmalarda internet bağımlılık düzeyi yüksek olan ve problemli internet kullanımı olan ergen çocukların sosyal beceri alanlarında, davranışsal ve sosyal ilişki problemleri yaşama olasılıklarının daha yüksek olduğunu ortaya koymaktadır (18,25,38,45,46) Kesitsel tasarımı nedeniyle tek bir zaman diliminde ölçümlerin yapılması ve veriler katılımcıların kendi beyanları ile toplanması bu çalışmanın sınırlılığıdır.…”
Section: Discussionunclassified
“…Bu durum, gerçek hayattan uzaklaşmasına sosyal, akademik, mesleki ve kişiler arası ilişkilerinde sorun yaşamasına ve verimliliğinin düşmesine neden olmaktadır. 12,16,34,35 Yaşadığı bu problemler, kişilerin öz-etkililik-yeterlik algılarının azalmasına yol açmaktadır.…”
Section: Discussionunclassified